145k views
25 votes
2(x+11) = -26 show all work pls

User Eevar
by
5.0k points

1 Answer

10 votes

Answer:

x = -24

Explanation:

First, distribute 2 to all terms within the parenthesis:

2(x + 11) =

2 * x = 2x

2 * 11 = 22

2x + 22 = -26

Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS. PEMDAS is the order of operations, and stands for:

Parenthesis

Exponents (& Roots)

Multiplications

Divisions

Additions

Subtractions

~

First, subtract 22 from both sides of the equation:

2x + 22 (-22) = -26 (-22)

2x = -26 - 22

2x = -48

Next, divide 2 from both sides of the equation:

(2x)/2 = (-48)/2

x = -48/2

x = -24

x = -24 is your answer.

~

User Fer Martin
by
5.1k points